Analisis Manajemen Non Formal Lembaga Kursus dan Pelatihan di Kota Jambi - Wahyudi, Nur Siddiq; Taufik, Muhammad; Patoni, Ahmad; Ardianhsa, Yashid Wirya (Jurnal Ilmiah Dikdaya, 2024)
This research aims to provide insight regarding observations of course and training institutions in Jambi City to readers and observers to understand how to analyze observations of course and training institutions in Jambi City. This research was carried out in various places in Jambi City. The time this research was conducted was April 21 202. This research is a qualitative descriptive research, namely natural. Data collection techniques are triangulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. The approach uses a qualitative approach, namely an approach that describes the data descriptively. The results of this research are that each institution has different management for sewing/embroidering clothes courses. After completing the training, participants can open their own sewing or embroidering customer clothes business and have been certified by the previous training place. With assistance from the government, it can ease the burden on participants in achieving training, so this assistance can also enable activities at course institutions to run smoothly and effectively